Measurement of Dabigatran Concentration Using Finger Prick Dried Blood Spot Sample Collection - Lin, Shin-Yi; Peng, Yu-Fong; Huang, Chih-Fen; Kuo, Ching-Hua; Tang, Sung-Chun; Jeng, Jiann-Shing (Frontiers in Pharmacology, 2021)
Background and Purpose: Real-world laboratory monitoring of dabigatran activity is challenging. The purpose of the present study was to demonstrate the feasibility and accuracy of finger prick sampling with dried blood spot (fpDBS) cards in measuring the dabigatran concentration. Material and Methods: Patients >20 years of age with atrial fibrillation and receiving dabigatran therapy for more than 7 days were included in the study. Peak and trough dabigatran concentrations were collected by simultaneous finger prick and venous puncture. The dabigatran concentration was measured by ultra-high performance liquid chromatography with tandem mass spectrometry. Our previously developed post-column infused internal standard (PCI-IS) method was applied to estimate the blood spot volume on fpDBS and to calibrate the drug concentration. Deming regression was used to analyze the correlation between dabigatran concentration on fpDBS cards and in plasma samples, followed by Bland−Altman analysis to compare the bias between two sampling techniques. Results: A total of 33 patients were enrolled and contributed 66 plasma and 55 fpDBS dabigatran samples. The average patient age was 74.6±7.9 years, mean creatinine clearance 58.1±18.3 mL/min, and CHA2DS2-VASc score 3.5±1.6 points. The dabigatran concentration ranged from 41.8 to 1421.7 ng/mL. The plasma and DBS dabigatran concentrations correlated well (r= 0.98), and the conversion factor for fpDBS to plasma dabigatran concentration was 1.28. The Bland−Altman analysis showed that 94.5% of the fpDBS-predicted concentration fell within 20% of bias. Conclusion: The study showed that fpDBS measurement of dabigatran concentration is reliable and can be applied in clinical scenarios.